" الاستثمار التعليمي في رأس المال البشري ومدى ملائمته لمتطلبات سوق العمل في سورية" - عامر, وليد; موسى, نرمين (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يعتبر التعليم بمستوياته المختلفة إحدى الركائز الأساسية للتنمية البشرية، وأداة هامة لتأهيل القوى البشرية لدخول سوق العمل بالشكل الذي يساهم في تحسين ظروفهم الحياتية والمعيشية, خاصة التعليم الجامعي كونه يمثل قمة الهرم التعليمي. لذلك يهدف البحث إلى التَعرف على مفهوم الاستثمار التعليمي في رأس المال البشري وأيضا التعرف لمفهوم سوق العمل, كما يتناول بالعرض والتحليل تطور واقع التعليم الجامعي في الجمهورية العربية السورية, من خلال تحليل المؤشرات الكميَة والنوعيَة للتعليم العالي ومدى ملائمتها لمتطلبات سوق العمل للفترة ((2010-2000. وخلص البحث إلى: عدم المواءمة بين مخرجات التعليم العالي ومتطلبات سوق العمل في سورية, نتيجة انخفاض كفاءة مخرجات التعليم العالي كما ونوعا المتمثلة بارتفاع مؤشر عدم الاستفادة من الاستثمار التعليمي في رأس المال البشري . Education is one of the different levels of the main pillars of human development, and an important tool for the rehabilitation of manpower to enter the labor market in a way that contributes to improving their living conditions and living conditions, in particular university education it represents the top of the educational pyramid. Therefore research aims to identify the concept of investment education in human capital and also recognize the concept of the labor market, also addresses the supply and analysis evolution and the reality of university education in the Syrian Arab Republic, through the analysis of quantitative and qualitative indicators of higher education and their suitability to the requirements of the labor market for the period (2000, 2010). The research found: mismatch between higher education outputs and labor market requirements in Syria, as a result of the low efficiency of the outputs of higher education and as a sort of lack of access to higher education investment in human capital index.